Increase in Central Retinal Edema after Subthreshold Diode Micropulse Laser Treatment of Chronic Central Serous Chorioretinopathy - Maciej Gawęcki (Case Reports in Ophthalmological Medicine)
Purpose. Subthreshold diode micropulse laser (SDM) treatment is believed to be safe method of treating clinical entities involving retinal edema. We present a case of serous edematous reaction of the retina to SDM treatment. Methods. Case report. Results. A patient with chronic central serous chorioretinopathy (CSCR) was treated with SDM Yellow multispot laser. Procedure had been preceded by careful titration of the laser power, which after achieving of the threshold parameter was decreased by 50%. The follow-up visit two days after treatment revealed significant central retinal edema and subretinal fluid. Fundus autofluorescence image showed thermal reaction from the RPE in the form of small spots of hyperfluorescence corresponding to the laser multispot pattern used for treatment. Retinal edema resolved after topical bromfenac and single intravitreal bevacizumab injection. Slight pigmentary reaction from the RPE persisted. Conclusion. In the treatment of CSCR, there is a need to significantly reduce threshold SDM power parameters or simply use very low power without titration.